Patterns of tubb2b Promoter-Driven Fluorescence in the Forebrain of Larval Xenopus laevis - Daume, Daniela; Offner, Thomas; Hassenklöver, Thomas; Manzini, Ivan (Frontiers in Neuroanatomy, 2022)
Microtubules are essential components of the cytoskeleton of all eukaryotic cells and consist of α- and β-tubulin heterodimers. Several tissue-specific isotypes of α- and β-tubulin, encoded by distinct genes, have been described in vertebrates. In the African clawed frog Xenopus laevis, class II β-tubulin (tubb2b) is expressed exclusively in neurons, and its promoter was used to establish different transgenic frog lines. However, a thorough investigation of the expression pattern of tubb2b has not been carried out yet. Here, we describe the expression of tubb2b-dependent Katushka fluorescence in the forebrain of premetamorphic Xenopus laevis at cellular resolution. To determine the exact location of Katushka-positive neurons in the forebrain nuclei and to verify the extent of neuronal Katushka expression, we used a transgenic frog line and performed several additional antibody stainings. We found tubb2b-dependent fluorescence throughout the Xenopus forebrain but not in all neurons. In the olfactory bulb, tubb2b-dependent fluorescence is present in axonal projections from the olfactory epithelium, cells in the mitral cell layer, and fibers of the extrabulbar system, but not in interneurons. We detected tubb2b-dependent fluorescence also in parts of the basal ganglia, the amygdaloid complex, the pallium, optic nerve, the preoptic area, and the hypothalamus. In the diencephalon, tubb2b-dependent fluorescence occurred mainly in the prethalamus and thalamus. As in the olfactory system, not all neurons of these forebrain regions exhibited tubb2b-dependent fluorescence. Together, our results present a detailed overview of the distribution of tubb2b-dependent fluorescence in neurons of the forebrain of larval Xenopus laevis and clearly show that tubb2b-dependent fluorescence cannot be used as a pan-neuronal marker.